Manajemen Badan Amil Zakat Nasional (BAZNAS) dalam Pemberdayaan Ekonomi Umat Melalui Zakat Produktif: Studi Kasus BAZNAS Kota Medan - Tina Banurea; Faridah Faridah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study examines the management of productive zakat conducted by the National Amil Zakat Agency (BAZNAS) of Medan City in empowering the economic conditions of mustahik (zakat beneficiaries). The study aims to analyze the management process of productive zakat and its impact on improving the economic independence of mustahik. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving purposively selected informants, including Ayub Siregar as the Head of Distribution and Utilization Division of BAZNAS Medan City, as well as productive zakat beneficiaries, namely Erwin, Bukhori, and Alam Sari. The findings reveal that BAZNAS Medan City manages productive zakat through beneficiary data collection and field surveys, distribution of business assistance in the form of carts and business equipment, as well as periodic supervision and evaluation of mustahik businesses. The productive zakat program has positively contributed to increasing income, supporting small business development, and improving the economic independence of mustahik. However, several challenges remain, including limited business experience, low entrepreneurial capacity, and the need for continuous business mentoring to ensure business sustainability among beneficiaries.